1997
DOI: 10.1177/1045389x9700800904
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Control System Using Electromagnetic Forces

Abstract: This paper presents the concept of a new vibration control system in which motions of an Al-Fe alloy thin beam/plate with magnetized segments can be suppressed or activated through electromagnetic forces induced by an applied electric current. Analytical evaluation of the induced electromagnetic forces acting both on the electric current applied and on the magnetized segments are derived from an electromagnetic consideration. To examine the feasibility of the proposed vibration control system, we have formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…Lee [11] studied the dynamic stability of conducting beam plates in a transverse magnetic field and demonstrated the existence of three regions of stability: damped stable oscillation, static asymptotic stability, and static divergence instability. Matsuzaki et al [12,13] proposed the concept of a new vibration control system in which the vibration of a partially magnetized beam is suppressed by using electromagnetic forces and performed an experimental study to show the effectiveness of their concept. Recently, Kwak et al [14] investigated the effects of an eddy current damper (ECD) on a cantilever beam, and their experimental results showed that an ECD can be an effective device for vibration suppression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee [11] studied the dynamic stability of conducting beam plates in a transverse magnetic field and demonstrated the existence of three regions of stability: damped stable oscillation, static asymptotic stability, and static divergence instability. Matsuzaki et al [12,13] proposed the concept of a new vibration control system in which the vibration of a partially magnetized beam is suppressed by using electromagnetic forces and performed an experimental study to show the effectiveness of their concept. Recently, Kwak et al [14] investigated the effects of an eddy current damper (ECD) on a cantilever beam, and their experimental results showed that an ECD can be an effective device for vibration suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several studies [10][11][12][13][14][15] have investigated the effects of magnetic fields on vibration in cantilever beams. Takagi et al [10] studied thin plate deflection in a magnetic field both analytically and through experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…Eddy current braking concept is also applied in dynamometers [3]. The benefits of magnetic drag force are employed to develop various damping elements [4][5][6][7] for operating without needs of electronic devices and external power supplies.…”
Section: Introductionmentioning
confidence: 99%
“…Lee [13] studied the dynamic stability of conducting beam plates in a transverse magnetic field and demonstrated the existence of three regions of stability: damped stable oscillation, static asymptotic stability, and static divergence instability. Matsuzaki et al [14,15] proposed the concept of a new vibration control system in which the vibration of a partially magnetized beam is suppressed by using electromagnetic forces and performed an experimental study to show the effectiveness of their concept.…”
mentioning
confidence: 99%
“…Additionally, there are several studies [12][13][14][15][16][17][18][19][20][21][22] that have investigated the effects of magnetic fields on vibration in cantilever beams. Lee [13] studied the dynamic stability of conducting beam plates in a transverse magnetic field and demonstrated the existence of three regions of stability: damped stable oscillation, static asymptotic stability, and static divergence instability.…”
mentioning
confidence: 99%